Moving figures : class and feeling in the films of Jia Zhangke - Schultz, Corey Kai Nelson (Edinburgh studies in East Asian film., 2018)
This book focuses on how the Reform Era' has been constructed in the work of the director Jia Zhangke, analysing the archetypal class figures of worker, peasant, soldier, intellectual and entrepreneur that are found in his films.